Population aging in the context of changing changes - Lange, Milena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aging of population is largely caused by falling fertility. To find out how fertility affects the share of the elderly people in the population, four variants of the UN World Population Prospects 2010 for Poland and Europe were examined, as well as selected indicators of population aging. The relatively high fertility and comparatively short life expectancy in Poland until the end of 1980s explain why its population aged much more slowly than other populations in Europe. In the last two decades the share of the elderly people kept increasing, mostly because of the deep decline in the number of births. For almost a decade now Poland has been one of the demographically old countries, although the aging process is relatively less pronounced in Poland than in Italy or Germany. In the medium variant of the UN forecast Polish fertility will be growing for the next few decades, but its level will not be high enough to ensure the minimum population replacement. Only in the high variant its growth will lead to rates of population reproduction higher than the minimum level. This situation might take place as early as the first half of the 2020s. The analysis of particular indicators illustrating the progress of demographic aging leads to a conclusion that even high fertility will not rejuvenate the age structure of Polish population, but it may considerably slow down the process of its aging.